Effects of Verbascoside Administration on the Blood Parameters and Oxidative Status in Jennies and Their Suckling Foals: Potential Improvement of Milk for Human Use - G. D'Alessandro, Angela; Casamassima, Donato; Jirillo, Felicita; Martemucci, Giovanni (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2014)
Background: Oxidative damage of tissues and cellular components is a primary or secondary cause of many human diseases and is associated with the welfare and productivity of farm animals. Natural antioxidants have gained attention for the prevention of oxidative damage-related diseases. Aim of the Study: To determine the effects of dietary supplementation with a natural polyphenol (verbascoside, VB) on the serum lipid profile, the hepatic functionality and oxidative status of jennies and their suckling foals. Results: Supplementation with VB over 30 days decreased in jennies the serum levels of total cholesterol, LDL cholesterol, triglycerides, bilirubin, AST and ALT, and it increased the HDL cholesterol. As markers of the oxidative status, a decrease of ROMs and TBARs, and an increase in vitamin E levels were observed. Interestingly, the suckling foals showed the same trends in the blood parameters and oxidative status. Conclusions: Supplementation with VB influenced the lipidic and hepatic profiles, and oxidative status of jennies and the suckling foals, and may represent a potentially novel strategy for improving the functional properties of donkey’s milk for human diet and for improving the welfare of young animals.
Keywords: donkeys